Overview of the Multiview and 3D Extensions of High Efficiency Video Coding - Tech, Gerhard; Ying Chen; Muller, Karsten; Ohm, Jens-Rainer; Vetro, Anthony; Ye-Kui Wang (IEEE transactions on circuits and systems for video technology, 2016)
The High Efficiency Video Coding (HEVC) standard has recently been extended to support efficient representation of multiview video and depth-based 3D video formats. The multiview extension, MV-HEVC, allows efficient coding of multiple camera views and associated auxiliary pictures, and can be implemented by reusing single-layer decoders without changing the block-level processing modules since block-level syntax and decoding processes remain unchanged. Bit rate savings compared with HEVC simulcast are achieved by enabling the use of inter-view references in motion-compensated prediction. The more advanced 3D video extension, 3D-HEVC, targets a coded representation consisting of multiple views and associated depth maps, as required for generating additional intermediate views in advanced 3D displays. Additional bit rate reduction compared with MV-HEVC is achieved by specifying new block-level video coding tools, which explicitly exploit statistical dependencies between video texture and depth and specifically adapt to the properties of depth maps. The technical concepts and features of both extensions are presented in this paper.